Fabrication And Optimization Of Cyanoacrylate Nanocomposites For Ion Beam Etching Process On Hard Disk Slider - Teoh, Hui Chiang (2018)
In this research, the ion beam etching (IBE) process which is used to fabricate a slider is expected to increase the etching rate of IBE. The low thermal and electrical conductivities of cyanoacrylate has to be improved to facilitate the heat transfer efficiently during IBE process and avoid the slider’s reader to be damaged by electrostatic discharge (ESD) effect. Therefore, the aim of the study is to improve thermal and electrical conductivities cyanoacrylate by addition of carbon based nanofillers (graphene, multi walled carbon nanotubes (MWCNTs) and graphite nanoparticles). Carbon nanofillers filled cyanoacrylate nanocomposites were fabricated using ultrasonication and mould casting techniques. It was found that graphene and MWCNTs are able to enhance the thermal conductivity by 204 % and 233% of the cyanoacrylate, respectively, but not graphite nanoparticles. The thermal conductivity of cyanoacrylate nanocomposite was enhanced to a maximum value when increasing the amount of nanofillers loading but further increment of nanofillers decreased the thermal conductivity. It was also found out that only MWCNTs decreased the surface and volume resistivities of cyanoacrylate nanocomposite when nanofillers loading was increased from 0.1 to 0.5 vol.%. The optimized hybrid fillers/cyanoacrylate nanocomposite with graphene and MWCNTs achieved research target through design of experiments (DOE) with thermal conductivity of 0.3881 W/mK, surface resistivity of 7.97 x 106 Ω/sq, volume resistivity of 3.35 x 107 Ω.m, and tribocharge of 12 V. However, the tensile strength, ultimate tensile strain and Shore D hardness of optimized cyanoacrylate nanocomposite were decreased as compared to neat cyanoacrylate by 44%, 53% and 18%, respectively. The tensile modulus and maximum shear strength of adhesive lap joint test were statistically equivalence for neat cyanoacrylate and optimized cyanoacrylate nanocomposite. The optimized cyanoacrylate nanocomposite showed improvement in thermal degradation as compared to neat cyanoacrylate. The performance of three inch pallet (TIPs) which applied the optimized cyanoacrylate nanocomposites were improved in heat transfer because no slider with burn defects was found with high etching rate.